Optimizing Female Soccer Players Dribbling Performance Using Lower And Upper Body Plyometrics - Uzor, Theresa Nkiru; Ujuagu, Nonye Ann (S&Co Publishing, 2025)
The study aims to examine the effectiveness of lower and upper body plyometrics on performance of dribbling skill among female soccer players. This study adopted a quasi-experimental research design, pre-test, post-test and control group. To facilitate the study, three research questions and three null hypotheses guided the study. The population of the study comprised of thirty-two female soccer players in Nnamdi Azikiwe University, Awka, who have participated in outside competition and belong to the school soccer team. Twenty-one female students aged 14-18years volunteered to participate in the study. No sample was used since the population was small. Data collected were analyzed using arithmetic mean and standard deviation, while t-test inferential statistics was used for testing the hypothesis at 0.05 level of significant. The findings revealed that lower and upper body plyometrics have positive effect on dribbling skill among female soccer players in the game soccer. The study concluded that using lower and upper body plyometrics have great effect on performance of dribbling skill among female soccer players in the game of soccer. Based on the findings, it was recommended that coaches and athletes should include lower and upper body plyometrics using squat jumps and plyo push-ups in their training schedule order to improve dribbling skill in the game of soccer.